Integrative taxonomy of introduced Haplosclerida and four new species from Hawaiʻi - Vicente, Jan; Rutkowski, Emily; Lavrov, Dennis V.; Martineau, Gabrielle; Timmers, Molly; Toonen, Robert J. (Zootaxa, 2025)
Haplosclerid sponges (Porifera: Demospongiae: Heteroscleromorpha), and particularly the family Chalinidae, are notoriously difficult to identify through taxonomic methods alone. Here we use an integrative approach to confirm the identification and report both polymorphic characters and different morphotypes exhibited from a recruitment stage that complicate identification of introduced haplosclerid species Haliclona (Soestella) caerulea and Gelliodes conulosa sp. nov. in Hawaiʻi. Using these same methods, we also describe three new species Haliclona (Gellius) pahua sp. nov., Haliclona (Reniera) kahoe sp. nov., Haliclona (Rhizoniera) loe sp. nov. from our collections in Kāne‘ohe Bay. Using a combination of mitochondrial and ribosomal RNA sequences, we compile a phylogeny that is consistent with previous molecular work but is at odds with the morphological characters used to classify species belonging to Chalinidae and Niphatidae families within Haplosclerida. Although shared morphological traits were distributed across taxa throughout the tree, both mitochondrial and ribosomal RNA sequences were diagnostic, with an average of at least 3 % sequence divergence among species and their closest relative. This study highlights both the use of standardized Autonomous Reef Monitoring Structures (ARMS) to access the hidden diversity of haplosclerid sponges, and the potential for competition between these introduced and newly described and potentially endemic species.